2016
DOI: 10.1007/s13592-016-0442-x
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time-dependent effects of oral octopamine treatments on the sucrose responsiveness in stingless bees (Melipona scutellaris)

Abstract: -Biogenic amines modulate physiological responses and, consequently, the behaviour of animals. Here, we present the first pharmacological approach to evaluate the influence of octopamine (OA) in stingless bees (Apidae, Meliponini), a group of highly eusocial bees distributed in the tropical and southern subtropical areas of the globe. In sucrose response threshold assays, foragers of Melipona scutellaris showed an increased responsiveness to sucrose after oral OA treatments. The effect of OA on the bees' respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Only for octopamine are some data available. In M. scutellaris octopamine increases gustatory responsiveness similar to honeybees [McCabe et al, 2017]. In another stingless bee, Plebeia droryana, octopamine treatment increases the number of bees at artificial sucrose feeders, which was interpreted by an octopaminedriven lowering of the individual sucrose response threshold [Peng et al, 2020], similar to the effect observed in honeybees [Barron et al, 2002;Barron and Robinson, 2005].…”
Section: Discussionmentioning
confidence: 72%
“…Only for octopamine are some data available. In M. scutellaris octopamine increases gustatory responsiveness similar to honeybees [McCabe et al, 2017]. In another stingless bee, Plebeia droryana, octopamine treatment increases the number of bees at artificial sucrose feeders, which was interpreted by an octopaminedriven lowering of the individual sucrose response threshold [Peng et al, 2020], similar to the effect observed in honeybees [Barron et al, 2002;Barron and Robinson, 2005].…”
Section: Discussionmentioning
confidence: 72%
“…This raises the question whether OA plays similar roles in stingless bees as in honeybees. We are aware of only one study that has explored the effects of OA in stingless bees: Mc Cabe et al [21] found that in the stingless bee Melipona scutellaris, workers treated with OA showed an increased sucrose responsiveness, similar to what has been found in A. mellifera [21,22]. They found both timeand dose-dependent effects of OA on sucrose responsiveness.…”
Section: Introductionmentioning
confidence: 73%
“…At the treatment feeder, we added 0.01 M OA (Sigma Adrich), whereas the control feeder did not offer OA (Colonies that were offered an OA feeder during the treatment phase will be called OA colonies, whereas colonies offered only sucrose solution will be called control colonies). This OA concentration effectively lowered the sucrose response threshold in M. scutellaris [21] and recruitment communication in honeybees [11]. The treatment period lasted 60 min, during which all marked and unmarked bees at the feeders were counted at 5 min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of a gene encoding the octopamine receptor (Amoctβr3/4) changes with age rather than with social task, whereas that of Amoctαr1 correlates with social tasks (Reim and Scheiner, 2014). Octopamine can also enhance sugar responses in the proboscis extension of the honey bee (Scheiner et al, 2002) and the stingless bee Melipona scutellaris (McCabe et al, 2017), which is a behavioral modulation for foraging characteristics. In fact, octopamine increases individual foraging effort and collective food source exploitation in the neotropical stingless bee Plebeia droryana (Peng et al, 2020).…”
Section: From Nursing To Foragingmentioning
confidence: 99%